Analysis of phasor measurement method in tracking the power frequency of distorted signals - Agha Zadeh, R.; Ghosh, Arindam; Ledwich, G.; zare, F. (The Institution of Engineering and Technology, 2010)
This study presents an analysis of phasor measurement (PM) method for tracking the fundamentalpower frequency to show if it has the performance necessary to cope with the requirements of power system protection and control. In this regard, several computer simulations presenting the conditions of a typical power system signal especially those highly distorted by harmonics, noise and offset, are provided to evaluate the response of the PM technique. A new method, which can shorten the delay of estimation, has also been proposed for the PM method to work for signals free of even-order harmonics.